Legal Analysis of the Decision on a Hit-and-Run Traffic Accident Case in Semarang: Case Study of District Court Decision No. 386/Pid.Sus/2023/PN.Smg - Melinda Putri Lutfi Cahyani; Kurniasari, Ela (Arkus, 2024)
The hit-and-run case that killed Selvi Amalia Nuraeni by Kevin Meikacandra has attracted public attention. This research aims to analyze the judge's decision in this case (Decision Number 386/Pid.Sus/2023/PN.Smg.) and provide its implications for law enforcement and public safety. This research uses a normative method with a statutory approach and a case approach. Secondary data consisting of primary and secondary legal materials is analyzed using a deductive mindset. The judge's decision in the Kevin Meikacandra case shows that the judge considered various factors, including elements of negligence, intentionality and the community's sense of justice. The judge sentenced Kevin Meikacandra to 4 years in prison, which was considered a light sentence by some in the community. The judge's ruling in this case has important implications for law enforcement and public safety. On the one hand, this decision shows that the judge is trying to provide justice for all parties. On the other hand, this decision also shows that there are still gaps in the legal system that allow hit-and-run perpetrators to receive light sentences.